Subset of individuals with autism spectrum disorders and extreme macrocephaly associated with germline PTEN tumour suppressor gene mutations. Issue 4 (1st April 2005) - Butler, M G; Dasouki, M J; Zhou, X-P; Talebizadeh, Z; Brown, M; Takahashi, T N; Miles, J H; Wang, C H; Stratton, R; Pilarski, R; Eng, C
Abstract : The genetic aetiology of autism remains elusive. Occasionally, individuals with Cowden syndrome (a cancer syndrome) and other related hamartoma disorders such as Bannayan-Riley-Ruvalcaba syndrome, Proteus syndrome, and Proteus-like conditions, are characterised by germline PTEN mutations, and may have neurobehavioural features resembling autism as well as overgrowth and macrocephaly. Therefore, we undertook PTEN gene mutation analysis in 18 subjects mainly prospectively ascertained with autism spectrum disorder and macrocephaly. Of these 18 autistic subjects (13 males and five females; ages 3.1–18.4 years) with a head circumference range from 2.5 to 8.0 standard deviations above the mean, three males (17%) carried germline PTEN mutations. These three probands had previously undescribed PTEN mutations: H93R (exon 4), D252G (exon 7), and F241S (exon 7). They had the larger head circumference measurements amongst all our study subjects. The three residues altered in our patients were highly evolutionarily conserved. We suggest that PTEN gene testing be considered for patients with autistic behaviour and extreme macrocephaly. The gene findings may impact on recurrence risks as well as medical management for the patient.